The Advaitic Theism of he Bhagavata Purana - Kadankavil, Thomas (Journal of Dharma, 1988)
Daniel P. Sheridan, The Advaitic Theism of he Bhagavata Purana, Delhi: Motilal Banarsidass, 1986, pp. 170, Rs. 75/-